2008
DOI: 10.1111/j.1741-3737.2008.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Generative Ritual Among Nonmetropolitan Lesbians and Gay Men: Promoting Social Inclusion

Abstract: Generativity is typically studied as a normative adult inclination expressed through social roles (D.P. McAdams & E. de St. Aubin, 1992). We extend this research by examining generativity through the lenses of social marginality and ritual. Toward this end, we utilize in‐depth interview and observational data about family rituals from 49 downstate Illinois residents who participated in a larger survey of nonmetropolitan lesbian and gay life. We first examine their ritual intentions and the locations where they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…These findings affirm previous research on generativity, which has found that nonmetropolitan gay men and lesbians often acted on generative concerns (Oswald & Masciadrelli, 2008). Furthermore, our findings relate to generativity theories, particularly recent research on generativity among nonmetropolitan LGBTQ individuals (Oswald & Masciadrelli, 2008;Paceley et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings affirm previous research on generativity, which has found that nonmetropolitan gay men and lesbians often acted on generative concerns (Oswald & Masciadrelli, 2008). Furthermore, our findings relate to generativity theories, particularly recent research on generativity among nonmetropolitan LGBTQ individuals (Oswald & Masciadrelli, 2008;Paceley et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Most studies of generativity have focused on heterosexual individuals in mid-life and describe generativity as the provision of institutions and resources out of concern for future generations (McAdams & St. Aubin, 1998). Research with nonmetropolitan LGBTQ individuals found that generativity was linked to bringing broader community awareness to LGBTQ issues, motivations based in religion, and role demands, such as being a parent (Oswald & Masciadrelli, 2008). Paceley, Oswald, and Hardesty (2014) also examined the concept of generativity and found that individuals in nonmetropolitan areas who felt emotional attachments to the LGBTQ community were more likely to become involved in different types of LGBTQ organizations including political, professional, religious, and social organizations, as well as community centers.…”
Section: Motivations For Community Involvementmentioning
confidence: 97%
“…The research of Turner et al (2015) revealed a focus on family, patience, tolerance, and love as common values in the narratives of their focus group participants. These caregiving priorities are relevant to altruism and the transgenerational sharing of history in broader LGBTQ elderly community family networks (Oswald & Masciadrelli, 2008). Interestingly, however, Turner et al point to a positive role of the often-criticized biomedical model.…”
Section: The Social Worker Role In Transdisciplinary Teamsmentioning
confidence: 99%
“…In addition, compounded stigma resulting from ethnic and LGBTQ identity is often sufficient to keep the clients themselves from seeking medical attention. Their difficulties are further exacerbated when health care professionals are ignorant about the complex needs of multiple subjugated identities (Gratwick, Jihanian, Holloway, Sanchez, & Sullivan, 2014;Oswald, & Masciadrelli, 2008;Pasupathi et al, 1995;Turner et al, 2015). It is for this reason that the Partnership for Health and Aging sponsored by the American Geriatric Society (Young et al, 2011) has convened 20 participating organizations to improve elder care.…”
Section: Force Field Analysis: Exploring the Driving And Restraining mentioning
confidence: 99%
See 1 more Smart Citation